A Methodology for Validating Safety Heuristics Using Clinical Simulations: Identifying and Preventing Possible Technology-Induced Errors Related to Using Health Information Systems. (31st March 2013) - Borycki, Elizabeth; Kushniruk, Andre; Carvalho, Christopher
Abstract : Internationally, health information systems (HIS) safety has emerged as a significant concern for governments. Recently, research has emerged that has documented the ability of HIS to be implicated in the harm and death of patients. Researchers have attempted to develop methods that can be used to prevent or reduce technology-induced errors. Some researchers are developing methods that can be employed prior to systems release. These methods include the development of safety heuristics and clinical simulations. In this paper, we outline our methodology for developing safety heuristics specific to identifying the features or functions of a HIS user interface design that may lead to technology-induced errors. We follow this with a description of a methodological approach to validate these heuristics using clinical simulations.